Women in prison: the Bangkok rules and beyond = Femmes en prison : les règles de Bangkok et au-delà - Kempen, P. H. P. H. M. C. van (Publication, 2017)
Women are a rapidly growing minority in prisons. Prison systems, however, have always been determined by the behaviour of men. The 2010 UN Bangkok Rules form a body of rules that is specifically aimed at the needs of women in prison. Being the first international instrument on this subject, the Bangkok Rules can be considered a milestone. Thus this volume focuses on the topic of women in prison in general, and on the Bangkok Rules in particular. The volume comprises an introductory chapter, seven thematic chapters, and 23 chapters dedicated to individual countries around the world. Themes discussed in these chapters include, among others, the (international) human rights framework applicable to women in prison, statistics and criminological factors relevant to women in prison, and the actual conditions of women in prison worldwide. An extensive collection of expert knowledge, this volume intends to highlight both good practice in the context of women in prison and the many challenges that lie ahead